DNA Methylation and microRNA patterns are in association with the expression of BRCA1 in ovarian cancer - Shariati-Kohbanani, M; Zare-Bidaki, M; Taghavi, M M; Taghipour, Z; Shabanizadeh, A; Kennedy, D; Dahim, H; Salahshoor, M R; Jalili, C; Kazemi Arababadi, M (Cellular and Molecular Biology, 2016)
Ovarian cancer is the sixth most prevalent cancer in women and is considered the most lethal gynecological malignancy. It can be inherited as a familial disease but also has a strong spontaneous occurrence. Although the disease is associated with genome instability brought on by genetics and environmental factors there is evidence that mutations in the gene encoding for the breast cancer type 1 susceptibility protein (BRCA1) or its down-regulation are involved in its development. Down-regulation of BRCA1 expression by hypermethylation of its promoter may account for some cases of ovarian cancer but this does not explain the cause of the majority of the disease. This review explores the role of BRCA1 promoter hypermethylation and micro-RNAs (miRNA) involved in the regulation of BRCA1 and their role in ovarian cancer development as well as some of the exciting discoveries which could lead to targeting miRNA with a view to restoring BRCA1 expression in diseased tissues.